Lewis Acid Enhancement of Gold Catalytic Activity Through Counterion Coordination. Synthesis of Benzofulvenes from Progargylsilanes and Benzophenones. Issue 7 (11th March 2022) - Fernández, Sergio; Santamaría, Javier; Ballesteros, Alfredo
Abstract: A simple, regioselective and high yielding gold‐catalyzed synthesis of benzofulvenes, from progargylsilanes and benzophenones, is described. Initially, the carbonyl compound is synergistically activated by the silyl moiety and, for the cyclization step, the gold catalytic activity is clearly increased by the participation of aluminum trichloride, acting as a cocatalyst. Several mechanistic intermediates, such as enynes and silylbenzofulvenes, have been isolated. Different control experiments have been performed, indicating the participation of [LAu][NTf2 AlCl3 ] complex as the true catalyst, and revealing a dramatic enhancement of the gold activity by coordination of the Lewis acid to the gold counterion. Abstract :